291 Phase Ib study of selicrelumab (CD40 agonist) in combination with atezolizumab (anti-PD-L1) in patients with advanced solid tumors. (9th November 2020) - Barlesi, Fabrice; Lolkema, Martijn; Rohrberg, Kristoffer Staal; Hierro, Cinta; Marabelle, Aurelien; Razak, Albiruni Abdul; Teixeira, Luis; Boni, Valentina; Miller, Wilson H; Aggarwal, Charu; Stern, Martin; Cirovic, Olivera; et al.
Abstract : Background: Selicrelumab is a human IgG2 agonistic anti-CD40 monoclonal antibody. Binding of the antibody to CD40 expressed on antigen-presenting cells results in T- cell priming and T-cell dependent anti-tumor activity. In response to T-cell activation, tumor cells express programmed-death ligand 1 (PD-L1) that can suppress effector T-cells. Atezolizumab interrupts this feedback loop by blocking PD-L1, thereby supporting the combination with selicrelumab. Methods: This phase Ib open-label, multicenter, dose escalation (DE)/expansion clinical study (NCT02304393 ) investigated safety, pharmacokinetic (PK), pharmacodynamics (PD) and efficacy of selicrelumab in combination with atezolizumab in unselected patients with advanced/metastatic solid tumors, not amenable to standard therapy. In DE cohorts, a single dose of selicrelumab was given, either by intravenous (IV) infusion at a 16 mg fixed dose or subcutaneously (SC) at a range from 1 to 64 mg/dose. In dose-expansion cohorts (small bowel and colorectal cancer, head and neck squamous cell carcinoma [HNSCC] and non-small cell lung carcinoma), patients received multiple doses of selicrelumab SC at a dose of 16 mg. In all treatment cohorts, patients received atezolizumab at a fixed dose of 1200 mg IV Q3W. Results: In this study, 140 patients were treated. This included 95 patients in DE cohorts (6 patients in the IV cohort, 89 patients in the SC cohorts) and 45 patients in dose-expansion cohorts. In the IV cohort, infusion related reaction was the most frequent treatment-related adverse event (TRAE; 50%), while Grade ≥ 3 TRAE occurred in 1 patient (16.7%). In this cohort one dose-limiting toxicity (DLT) was reported (Grade 3 pancytopenia). In the SC cohorts, the most frequent TRAE was injection site reaction (ISR; 92%). Four DLTs were reported in four patients: three Grade 3 ISR and one Grade 3 transaminase increase. Grade ≥ 3 TRAE were reported in 22 patients (16.4%). Anti-tumor activity was observed across cohorts receiving SC selicrelumab (dose range 1 to 36 mg). Eight of 80 evaluable patients in DE cohorts experienced objective responses (9% ORR). In the dose-expansion HNSCC cohort, three of 16 evaluable patients responded (15.8% ORR). There were no objective responses in the IV cohort. Treatment with selicrelumab resulted in significant peripheral B-cell depletion and activation and CD8+ T cell proliferation. Conclusions: Treatment with selicrelumab in combination with atezolizumab was well tolerated in patients with advanced solid tumors. Signals of clinical and PD activity were observed. However, efficacy of the combination in this unselected population was limited, when compared to monotherapy efficacy of atezolizumab. Trial Registration: NCT02304393 Ethics Approval: This study was approved by the local IRB at each participating study site.